THE ROLE OF PRECISION MEDICINE AND GENOMICS IN CARDIAC SURGERY - Michał Bereza; Kacper Kmieć; Edyta Szymańska; Mateusz Dembiński; Julia Prabucka-Marciniak; Patrycja Fiertek; Aleksandra Misarko; Hubert Rycyk; Jakub Pysiewicz; Marlena Rycyk (International Journal of Innovative Technologies in Social Science, 2025)
Background: Precision medicine, driven by advances in genomics, is reshaping the approach to diagnosis, risk assessment, and treatment planning in cardiac surgery. By analyzing genetic variation and molecular pathways, clinicians can move beyond standardized protocols toward individualized surgical care. Methods: This review synthesizes recent literature on the integration of genomic technologies - such as whole genome sequencing, gene expression profiling, and pharmacogenomics - into the preoperative, intraoperative, and postoperative phases of cardiac surgery. Sources include peer-reviewed articles, clinical trial data, and translational research reports published over the past 20 years. Results: Genomic profiling enables improved risk stratification, early detection of hereditary cardiovascular diseases, and identification of genetic biomarkers predictive of surgical outcomes. Pharmacogenomic insights allow optimization of perioperative drug therapy, reducing complications and enhancing recovery. Emerging applications include bioinformatics-driven surgical planning and integration of multi-omic data for real-time decision support. However, challenges remain regarding data interpretation, ethical considerations, and integration into clinical workflows. Conclusion: Precision medicine and genomics hold significant promise for improving patient-specific outcomes in cardiac surgery. Their successful implementation will require robust clinical evidence, interdisciplinary collaboration, and infrastructure to manage and interpret complex genomic data. Ongoing research is likely to expand their role from risk prediction to fully individualized surgical strategies.